Influence of water volume and heating temperatures on type of phases and crystallite size of sol-gel thin films deposited without solvent - Hanum Suzaim, Farah; Mohd Rosli, Zulkifli; Muhamad Juoi, Jariah (International Journal of Engineering and Technology, 2019)
Sol-gel parameters such as solvent, heating temperature and water volume play a role on affecting phase and crystallite size of Titanium Dioxide (TiO2) thin film. In this paper, the influence of water volume and heating temperature on phases and crystallite size were investigated. TiO2 thin films deposited without solvent by varying water volume which is 32 ml (W32) and 64 ml (W64) and heated at various heating temperature. The phases of TiO2 were analyzed by X-ray diffraction (XRD) and Raman Spectroscopy while crystallite size was calculated using Scherrer equation. Results show that when heating temperature at 500Â°C, W32 formulation exhibit anatase and rutile phases while W64 anatase and brookite phase were presence. Increment in heating temperature at 600Â°C, brookite phase in W64 formulation was transformed into rutile phase with crystallite size of 28.93 nm. Hence, the interest on preparing TiO2 coating without solvent is an alternative method towards green process.Â Â